Contextualizing early childhood literacy: lessons from Thailand’s nationwide reading initiative - Hareesol Khun-Inkeeree; Sarinda Puti (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study critically evaluates a three-book welfare initiative aimed at enhancing early childhood literacy across diverse regions in Thailand, addressing a gap in the literature concerning region-specific variations in program effectiveness. Utilizing a quantitative methodology, the study surveyed all 642 parents and caregivers of children aged 0-6 years across four regions, applying Bronfenbrenner’s ecological theory to assess changes in reading behaviors and family involvement pre- and post-intervention. Results showed a positive impact on reading habits and family engagement, yet revealed significant regional disparities, highlighting the influence of local socioeconomic and cultural factors on program outcomes. These findings emphasize the need for context-sensitive literacy programs tailored to the unique conditions of different regions to maximize effectiveness and reduce educational inequalities. The study concludes that while the welfare initiative shows promise, its varied impact suggests that more adaptable, region-specific interventions are necessary, and future research should incorporate longitudinal and qualitative analyses for a deeper understanding of early childhood literacy dynamics.